Hyperbilirubinemia in Preterm Infants Admitted to Neonatal Intensive Care Units in Ethiopia. (December 2020) - Aynalem, Sara; Abayneh, Mahlet; Metaferia, Gesit; Demissie, Abayneh G.; Gidi, Netsanet Workneh; Demtse, Asrat G.; Berta, Hailu; Worku, Bogale; Nigussie, Assaye K.; Mekasha, Amha; Tazu Bonger, Zelalem; McClure, Elizabeth M.; et al.
Background . Hyperbilirubinemia is prevalent and protracted in preterm infants. This study assessed the pattern of hyperbilirubinemia in preterm infants in Ethiopia. Methods . This study was part of multi-centered prospective, cross-sectional, observational study that determined causes of death among preterm infants. Jaundice was first identified based on clinical visual assessment. Venous blood was then sent for total and direct serum bilirubin level measurements. For this study, a total serum bilirubin level ≥5 mg/dL was taken as the cutoff point to diagnose hyperbilirubinemia. Based on the bilirubin level and clinical findings, the final diagnoses of hyperbilirubinemia and associated complications were made by the physician. Result . A total of 4919 preterm infants were enrolled into the overall study, and 3852 were admitted to one of the study's newborn intensive care units. Of these, 1779 (46.2%) infants were diagnosed with hyperbilirubinemia. Ten of these (0.6%) developed acute bilirubin encephalopathy. The prevalence of hyperbilirubinemia was 66.7% among the infants who were less than 28 weeks of gestation who survived. Rh incompatibility ( P  = .002), ABO incompatibility ( P  = .0001), and sepsis ( P  = .0001) were significantly associated with hyperbilirubinemia. Perinatal asphyxia ( P -value = 0.0001) was negatively associated with hyperbilirubinemia. Conclusion. The prevalence of hyperbilirubinemia in preterm babies admitted to neonatal care units in Ethiopia was high. The major risk factors associated with hyperbilirubinemia in preterm babies in this study were found to be ABO incompatibility, sepsis, and Rh isoimmunization.